Combination of deep breathing relaxation techniques and aromatherapy to reduce pain in patient with thoracic myeloradiculopathy: a case report - Isna Hanifah; Dyah Setyorini; Eka Afrima Sari (Journal of Health Management and Pharmacy Exploration, 2023)
Thoracic myeloradiculopathy is a gradual loss of nerve function caused by spinal cord tumor metastases at the thoracic level resulting in pain and reduced sensation or paralysis. Mrs. N, 59 years old with thoracic myeloradiculopathy, has acute pain as the main nursing problem. The patient has been given pharmacological pain management by administering the analgesic paracetamol 3×500 mg. Acute pain in patients with thoracic myeloradiculopathy can occur in all phases of treatment which causes additional days of treatment so it is necessary to provide complementary therapy which can reduce the days of hospitalization. One of the nonpharmacological complementary therapies that have been proven effective in relieving pain in patients with thoracic myeloradiculopathy is a combination of deep breathing relaxation techniques using aromatherapy. Aromatherapy is given to the patient by dripping an essential oil containing Lavandula angustifolia (lavender), Citrus nobilis (mandarin orange), and Origanum majorana (marjoram) onto cotton and inhaled by the patient. Implementation is carried out once during a 7-day treatment period with a duration 0f 20-30 minutes after the patient performs personal hygiene or when going to rest. The evaluation results showed that the patient's pain scale decreased significantly from a score of 4 to a score of 2. Giving a combination of deep breathing relaxation techniques and aromatherapy is effective in reducing pain complaints in patients with thoracic myeloradiculopathy in addition to pharmacological therapy given by the medical team).